Study of splenectomies for external trauma - Perrier, José (Cirugía del Uruguay, 1986)
The change of the therapeutic policy in case of trauma of the spleen, motivated a review of splenectomies (a total of 347) performed al the Hospital de Clínicas in ten years (1972-1982). Analyzed were the different etiological causes, manner of presentation, lesions associated ·with thi